Feeding Flaxseed and Lupins during the Transition Period in Dairy Cows: Effects on Production Performance, Fertility and Biochemical Blood Indices - Ioannis Nanas; Stella Dokou; Labrini V. Athanasiou; Eleni Dovolou; Thomas M. Chouzouris; Stelios Vasilopoulos; Katerina Grigoriadou; Ilias Giannenas; Georgios S. Amiridis (Animals, 2023)
Flaxseed and lupin seed were offered as an alternative dietary approach in dairy cows, through the partial substitution of soybean meal. Milk production and fertility traits were investigated. A total of 330 animals were allocated into two groups, treated (n = 176) and control (n = 154). From each group, 30 animals were selected for hematological and cytological studies. The experimental feeding period lasted for 81 days (25 days prepartum and 56 days postpartum). The control ration (group C) contained corn, barley, soybean meal, rapeseed cake, corn silage and lucerne hay; whereas, in the treatment group (group T), 50% of the soybean meal was replaced by an equal mixture of flaxseed and lupins. The two rations were formulated to be isonitrogenous and isoenergetic. Milk samples were analyzed for chemical composition, somatic cell count (SCC) content and total colony forming units (CFU). Blood samples were collected, and serum was analyzed for non-esterified fatty acids (NEFA), acute phase proteins (haptoglobin and serum amyloid) and lipid oxidation indices, namely thiobarbituric-acid-reactive substances (TBARS) and catalase activity. To assess polymorphonuclear neutrophils (PMN) numbers, endometrial samples from each cow were collected on days 21 and 42. No difference was recorded between groups in milk yield (p > 0.05). In multiparous cows, NEFA (mMol/L) concentrations were significantly lower in group T than in group C on day 14 (p > 0.009) and on day 42 (p = 0.05), while no difference was detected in the group of primiparous cows. At all time points, serum TBARS and catalase values were similar in both groups (p > 0.05). Multiparous cows in group T expressed the first postpartum estrus and conceived earlier than cows in group C (p ≤ 0.05). Between days 21 to 42 postpartum, the PMN reduction rate was higher in group T animals (p ≤ 0.05). Acute phase protein levels were in general lower in group T animals, and at specific time points differed significantly from group C (p ≤ 0.05). It was concluded that the partial replacement of soybean meal by flaxseed and lupins had no negative effect on milk yield or milk composition, and improved cow fertility; which, along with the lower cost of flaxseed and lupins mixture, may increase milk production profitability.